First report of leaf spot of lentil caused by Alternaria tenuissima in India - MURALEEDHAR S. ASKI; T. PRAMEELA DEVI, LAKSHMAN PRASAD*, H.K. DIKSHIT (Indian Phytopathology, 2017)
Lentil (Lens culinaris) is an important pulse crop plant belonging to the family Fabaceae. Lentil leaves exhibiting pale to tan spots were observed in the breeding trial fields at Indian Agricultural Research Institute (IARI), New Delhi in Feb, 2015 (Fig. 1a.). Brownish spots on leaves later coalescing to form larger patches and consequently caused blighting of the entire leaves.